Feasibility and Significance of Preclinical Diagnosis in Hypertrophic Cardiomyopathy. Issue 6 (November 2015) - Efthimiadis, Georgios K.; Pagourelias, Efstathios D.; Hadjimiltiades, Stavros; Meditskou, Soultana; Karvounis, Haralampos; McKenna, William J.
Abstract : Preclinical diagnosis in hypertrophic cardiomyopathy (HCM) refers to the detection of functional or histopathological abnormalities in subjects who carry any HCM-causing gene mutation, before or even without the development of left ventricular hypertrophy [genotype(+)/phenotype(-)subjects]. The concept that HCM pathology may exist in the absence of left ventricular hypertrophy is quite old but the ability to recognize the presence of early myocardial changes is quite new. Lessons from animal models have shown that in experimental human HCM, myocardial cell mechanical dysfunction precedes histopathological changes, such as myocyte disarray, fibrosis, and hypertrophy. Several clinical reports have demonstrated that the majority of HCM genotype(+)/phenotype(-) subjects display myocardial functional or histopathological changes, such as reduced tissue Doppler imaging-derived systolic and diastolic velocities, abnormal electrocardiogram, cardiac magnetic resonance-visualized myocardial crypts, mitral leaflet elongation, and evidence of a fibrotic state, such as increased type I procollagen synthesis, cardiac magnetic resonance-increased myocardial extracellular volume, and late gadolinium myocardial enhancement. All these signs have been proposed as preclinical markers of HCM. At present the separation of such a group of subjects in the early phase of their disease provides the opportunity to test new therapies to prevent the development of fibrosis, hypertrophy, and dysfunction.